Exploring the impact of m6A modification on immune diseases: mechanisms and therapeutic implication - Chen, Yutong; Liu, Min; Lu, Miao; Luo, Linling; Han, Zhongyu; Liu, Xide (Frontiers in Immunology, 2024)
N 6 -methyladenosine (m 6 A) is a chemical modification of RNA and has become a widely discussed topic among scientific researchers in recent years. It is distributed in various organisms, including eukaryotes and bacteria. It has been found that m 6 A is composed of writers, erasers and readers and is involved in biological functions such as splicing, transport and translation of RNA. The balance of the human immune microenvironment is important for human health abnormalities. Increasing studies have found that m 6 A affects the development of immune diseases such as inflammatory enteritis and systemic lupus erythematosus (SLE) by participating in the homeostatic regulation of the immune microenvironment in vivo. In this manuscript, we introduce the composition, biological function, regulation of m 6 A in the immune microenvironment and its progression in various immune diseases, providing new targets and directions for the treatment of immune diseases in clinical practice.